ANALYSIS OF ACCESSIBILITY OF IFLA CHECKLIST STANDARDS FOR DISABLED LIBRARIES IN UNIVERSITY LIBRARIES PADANG STATE - Iqbal, Calista Salsabila; Nelisa, Malta (Departemen Informasi Perpustakaan dan Kearasipan, 2023)
This research aims to 1) Find out the accessibility analysis of the IFLA Checklist physical access standards for disabled users at the Padang State University Library. 2) Know the accessibility analysis of the IFLA Checklist media format standard for disabled users at the Padang State University Library. 3) Know the accessibility analysis of the IFLA Checklist service and communication standards for disabled users at the Padang State University Library. There are 3 results from this research, namely First, an analysis of the accessibility of the IFLA Checklist physical access standards for disabled users in the Padang State University library shows that it is almost in accordance with the IFLA Checklist standards, because it obtained an average score of 2.91 or is on an interval scale of 2.7-3 .6. Second, the accessibility analysis of the IFLA Checklist media format standard for disabled users at the Padang State University library is not in accordance with IFLA standards because it obtained an average value of 2.62 which is on an interval scale of 1.9-2.7. Third, the accessibility analysis of the IFLA Checklist service and communication access standards for disabled users at the Padang State University library is not in accordance with IFLA standards because the average value is 2.62 which is on an interval scale of 2.8-3.6.